Two new species of Waldo Nicol, 1966 from sub-Antarctic waters (Bivalvia: Galeommatoidea) - Zelaya, Diego Gabriel (2013)
Two new sub-Antarctic Waldo species (Bivalvia) are described: Waldo digitatus and W. paucitentaculatus. Waldo digitatus has a large, elongateoval shell, with a short, horizontal dorsal margin, the valves showing a wide ventral gape, well separated from the anterior gape, and faint radial sculpture, fading toward shell margin. In addition, in this species the inhalant-pedal aperture is flanked by 515 pairs of tentacles. Waldo paucitentaculatus has a small, triangularoval shell, with anterior and posterior half of dorsal margin long, sloping gently at similar angles, the anterior and ventral shell gapes coalesce to form a single, narrow and elongated gape, and radial sculpture well-marked and visible from beaks to ventral margin. Another distinctive character is the presence of only 1 or 2 pairs of tentacles bordering the siphonal-pedal aperture. Both species were found living as epibionts on the heart sea urchin Abatus cavernosus: W. digitatus is restricted to the perioral area and W. paucitentaculatus is more widely distributed, mainly on the oral surface.